2022
DOI: 10.1177/15330338221111229
|View full text |Cite
|
Sign up to set email alerts
|

Can Lymphovascular Invasion be Predicted by Preoperative Contrast-Enhanced CT in Esophageal Squamous Cell Carcinoma?

Abstract: Objective: To explore whether preoperative contrast-enhanced computed tomogrpahy (CT) can predict lymphovascular invasion (LVI) in esophageal squamous cell carcinoma (ESCC), and provide a reliable reference for the formulation of clinical individualized treatment plans. Methods: This retrospective study enrolled 228 patients with surgically resected and pathologically confirmed ESCC, including 36 patients with LVI and 192 patients without LVI. All patients underwent contrast-enhanced CT (CECT) scan within 2 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Based on these viewpoints, LVI has great clinical guiding significance for the selection of treatment strategies in patients with SESCC. More importantly, LVI is difficult to be diagnosed before surgery and is mostly identified by postoperative pathological examination ( 17 ). However, prior studies on LNM in patients with SESCC included LVI as one of the predictive risk factors in statistical analysis ( 31 34 ), which may greatly limit the clinical application of the findings from these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these viewpoints, LVI has great clinical guiding significance for the selection of treatment strategies in patients with SESCC. More importantly, LVI is difficult to be diagnosed before surgery and is mostly identified by postoperative pathological examination ( 17 ). However, prior studies on LNM in patients with SESCC included LVI as one of the predictive risk factors in statistical analysis ( 31 34 ), which may greatly limit the clinical application of the findings from these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, LVI can greatly increase the risk of local malignant tumors micrometastasis ( 15 ) and lead to poor prognosis in patients with SESCC ( 16 ). However, almost all LVI is confirmed by postoperative histopathological examination, and it is extremely difficult to assess the status of LVI before surgery ( 17 , 18 ), which means that using LVI to make a preoperative prediction for LNM may be infeasible. So LNM and LVI should be integrated and considered as one outcome (it can be named LNM/LVI), and usable models for predicting the presence of LNM/LVI in patients with SESCC still have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Early recognition of high-risk recurrence patients is essential for the development of personalized ESCC treatment. Some studies ( 9 , 10 ) have used the image features of CT to predict the condition of LVI of esophageal cancer before surgery, but the accuracy of these morphological characteristics in predicting LVI is still not ideal, and it is hard to accurately reveal the tumor structural heterogeneity. Recently, radiomics and machine learning algorithms have been rapidly developed and widely used, which is an important development direction of tumor translational medicine in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography (CT) scanning is a commonly employed modality for the diagnosis and assessment of solid tumors [16]. The arterial phase images contain valuable information on tumor hemodynamics, which is closely linked to tumor activity and may offer insights into residual tumor survival based on contrast uptake [17][18][19]. Previous studies have indicated that radiomic features may be associated with the biological characteristics of the tumors [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%